Sense of Style: constructing identity and managing impressions on Lookbook.nu - Slemang, Zainab (Centre for Film and Media Studies, 2017)
This dissertation aims to explore how user-generated fashion content within the specific online community of Lookbook.nu is influenced by a set of underlying ideologies, such as beauty, power and gender to create specific and homogenous fashion identities in line with mainstream fashion trends, and which inform users' formation of identity within the structure of a community space. The aim of identifying the ideologies at play on the web site is to raise an awareness of how an individual's identity is influenced by others within his or her community space, even if that community happens to reside online. Furthermore, the means that inform the structures found on the community web site as well as the way in which the ideologies operate to maintain a certain criteria and level of fashion generated by users will be discussed in relation to identity formation. To determine how Lookbook users' perceive and portray identities on the site, semiology and multimodal discourse analysis were employed. It is important to keep in mind that while the media content in this thesis is as current as possible and while a great deal of content still exists on Lookbook, the platform is continuously evolving with new additions to its terms of use, mediums of access and overall design.